Upaya Guru dalam Menanamkan Nilai-Nilai Karakter - Oktavia Br Tarigan; Cherlizar Mulia Dewi; Rina Rahmi; Nur Rohman (Tematik: Jurnal Pendidikan Dasar Islam, 2025)
This study aims to analyze teachers' efforts in instilling character values in students at SD Paya Pelekung, Nagan Raya Regency. The approach used is qualitative with the type of field study through observational data collection techniques, in-depth interviews, and documentation. Data were analyzed using the Miles and Huberman interactive model which included data reduction, data presentation, and conclusion drawn, and tested for validity through triangulation of sources and techniques. The results of the study showed that teachers applied four main strategies, namely story-based learning and moral reflection, role models and habituation, social practice activities such as visits to orphanages and gardening activities, and strengthening through parental appreciation and involvement in child character development. These findings indicate that instilling character values will be more effective if it is carried out in an integrated, sustainable manner, and involves collaboration between schools, families, and the social environment.